Attribution of movement: Potential links between subjective reports of agency and output monitoring. Issue 5 (May 2015) - Sugimori, Eriko; Asai, Tomohisa
According to agency memory theory, individuals decide whether "I did it" based on a memory trace of "I am doing it". The purpose of this study was to validate the agency memory theory. To this end, several hand actions were individually presented as samples, and participants were asked to perform the sample action, observe the performance of that action by another person, or imagine performing the action. Online feedback received by the participants during the action was manipulated among the different conditions, and output monitoring, in which participants were asked whether they had performed each hand action, was conducted. The rate at which respondents thought that they themselves had performed the action was higher when visual feedback was unaltered than when it was altered (Experiment 1A), and this tendency was observed across all types of altered feedback (Experiment 1B). The observation of an action performed by the hand of another person did not increase the rate at which respondents thought that they themselves had performed the action unless the participants actually did perform the action (Experiments 2A and 2B). In Experiment 3, a relationship was observed between the subjective feeling that "I am the one who is causing an action" and the memory that "I did perform the action". These experiments support the hypothesis that qualitative information and sense of "self" are tagged in a memory trace and that such tags can be used as cues for judgements when the memory is related to the "self".